2008
DOI: 10.4103/0378-6323.45101
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in psoriasis: A study from south India

Abstract: The present study provides compelling evidence that psoriasis affects the quality of life, and it highlights the importance of adopting a multidimensional assessment of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
35
2
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 0 publications
15
35
2
9
Order By: Relevance
“…20,21 The prevalence of psychiatric morbidity reported in previous studies varies worldwide, ranging from 26.4% to 95%. [5][6][7]9,11 Earlier studies in India reported prevalence ranging from 30.2 to 84%. [6][7][8]11 A lower prevalence (35.2%) in our study may be explained as most of our patients were from rural background with less appearance related concern, as observed earlier.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…20,21 The prevalence of psychiatric morbidity reported in previous studies varies worldwide, ranging from 26.4% to 95%. [5][6][7]9,11 Earlier studies in India reported prevalence ranging from 30.2 to 84%. [6][7][8]11 A lower prevalence (35.2%) in our study may be explained as most of our patients were from rural background with less appearance related concern, as observed earlier.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7]9,11 Earlier studies in India reported prevalence ranging from 30.2 to 84%. [6][7][8]11 A lower prevalence (35.2%) in our study may be explained as most of our patients were from rural background with less appearance related concern, as observed earlier. 16 They found increased impairment with duration with disease which is in contradiction to our study and other studies 11 as it is reasoned that patients tend to adjust to the disease with time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas in studies supports the impact of psoriasis on the quality of life, while Kabbur H et al study reveals that the stress-reaction has impact on the exacerbations of psoriasis which in turn has effect on quality of life. [17][18][19][20][21] According to parameters of DLQI (symptom and feelings, work and school) quality of life was more affected in neurodermatitis compared to psoriasis. In patient with neurodermatitis the itching triggers the excessive concern and preoccupation of the illness.…”
Section: Discussionmentioning
confidence: 99%